Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 5 - Logarithmic, Exponential, and Other Transcendental Functions - 5.4 Exercises: 48

Answer

$y’=\frac{1}{2}(e^x+e^{-x})$

Work Step by Step

$y=\frac{1}{2}(e^x-e^{-x})$ let u=$e^x-e^{-x}$ u'=$e^x+e^{-x}$ $y=\frac{1}{2}u$ $y'=\frac{1}{2}u'$ $y’=\frac{1}{2}(e^x+e^{-x})$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.